Characterisation And Evaluation Of Pulp And Paper From Selected Ugandan Grasses For Paper Industry - Kamoga, Omar L. M.; Kirabira, J. B.; Byaruhanga, J. K.; Godiyal, R. D.; Anupam, Kumar (Cellulose Chemistry and Technology, 2016)
Non-wood fibrous materials and recycled fibres offer an opportunity to decrease or replace the use of wood fibres in the production of pulp and paper in countries with insufficient forest resources. The aim of this study was to characterise and evaluate the pulp and paper derived from four Ugandan grasses, namely Cymbopogon nardus, Paspalum notatum, Saccharum officinarum, and Digitaria scalarum, obtained using Soda-AQ and Kraft pulping methods for their potential use in the paper industry. The fibre morphology, as well as the physical properties, of both pulp and handmade paper sheets was analysed. The pulp and paper were identified with reasonable yield, medium viscosity, high bleachability, short and narrow fibres, and moderate paper strength. Saccharum officinarum pulp was characterised with high weighted average fibre length (1.143 mm), moderately high fibre width (18 μm), slenderness ratio (68), brightness (71.27%) and low kappa number (11.9); and the paper sheets with a tear index of 7.05 mNm2/g, while Cymbopogon nardus pulp was characterised with higher yield (44.20%), viscosity (915 cm3/g), low kinked fibre (20%) and curl (6%). The pulps from the two grasses superseded the others. Nevertheless, all the four grasses were recommended for pulp and paper production.
Keywords: Soda-AQ and Kraft pulping, fibre morphology, paper sheets, strength properties, sustainability